#TITLE_ALTERNATIVE# - ZULFIKAR (NIM : 13606010); Dosen Pembimbing: Dr. Djarot Widagdo Dr.Eng Arif Sugianto, HARINDRA
Turbine wheel of the APU GTCP-85 series used in B737 Classic has been returned to the engine shop for the investigation of possible failures indicated by the abnormal noise heard during operation. Thorough inspection found the damage of eroded blade tips. The maintenance procedure for the failure of the turbine wheel made of as cast nickel based superalloy INCONEL 792 is not available in the Aircraft Maintenance Manual (AMM) released by the manufacturer. To solve the problem, GMF Aero Asia as the holder of Design Organisation Approval (DOA) certificate proposed the repair procedure to overlay the damage part using electro-spark deosition (ESD) welding technique. Series of inspections and testing to the damaged part showed the possibility of damage started from fissures and microcracks and spreaded into an open-surface crack. The test development is conducted at a test coupon sheet made from the condemned turbine wheel. Solution treatment to normalize the microstructure of the condemned part from any previous cold work effects. was carried out before the ESD work. Since ESD cannot be used to joint the separate base metals required in preparing the tensile test specimens, brazing joint is used instead. Stress analysis using finite element method is performed to obtain the stress distribution due to operational loads. Centrifugal loading is applied on the model to simulate the operational 41700 rpm rotation of the turbine wheel. Acceptance criteria are assessed using radiography, tensile test, microhardness test, and metallography. The radiographic inspection showed no porosity on the ESD overlay. From the hardness test, the hardness of overlay is just a bit smaller from the hardness of base metal. Tensile tests specimens are broke not at the overlay but at the braze joint with fracture stress higher than the loading stress. The results can be interpreted that the bonding stress of overlay is higher than the loading stress. Metalography inspection also show virtually no heat affected zone (HAZ) created by ESD. Altogether it can be concluded that the acceptance criteria have been satisfied by the overlay using ESD.